Radiazione adattativa dei pesci antartici. Mappatura in situ di tratti evolutivamente rilevanti nel genoma dei Notothenioidei (IMAGES). - SCUDIERO, ROSARIA (2014)
Notothenioid fish are the result of adaptive radiation in the Southern Ocean, during oceanographic and ecological changes driven by the tectonics of the Antarctic continent. Remarkable biological and ecological modifications underlie the diversification and the evolutionary success of these fishes, presently recognized as prominent models in evolutionary/adaptive studies. In present project we will integrate sequence-based data from the available genomic resources with powerful in situ technologies, to provide patterns of genome structure and change in notothenioids over an evolutionary time scale. This will be achieved by physical mapping, onto the notothenioid chromosomal genomes, of marker sequences selected for their high informative value (AFGPs genes, sex-related sequences, iron metabolism genes, LINE sequences). The research aims at providing an comparative picture of the genome structure across notothenioid phylogeny to contribute to elucidate steps and mechanisms of genomic restructuring in this important animal model, over evolutionary time scale. The research contributes to the ongoing international effort towards our understanding of patterns and mechanisms of biological response to environmental change.